The importance of a notary public in UAE law - Aldhoori, Jasim Mousa; Sadat, Mohamed Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
There is no doubt that dealing among people is necessary for life continuing, whether inside the country or outside it, so it had to be found what preserve those treats according to it's shapes and picturesGod's wisdom required protect those relationships and treats via writing it by order, Hence the importance of the profession of a notary appeared or documentary in every country, in order to resolve strife between individuals to reach peace inside every family by writing it according to the legislation and law of each countryBecause of the importance of this rights and the necessity to prove it, there had to be an official way for people to resort toThe role of writer was not limited to documenting signatures, but also the role of a lawyer who protects rights by taking into account each individual interests with the willingness of the notary to assume full responsibility in the UAE legislator.
Keywords: public notary; private notary